Grow-out of spiny lobster Panulirus sp. with high stocking density in controlled tanks - Rio Yusufi Subhan; Eddy Supriyono; Widanarni, Widanarni; Daniel Djokosetiyanto (Jurnal Akuakultur Indonesia)
ABSTRACT